Autoimmune diseases and myelodysplastic syndromes. Issue 5 (4th April 2016) - Komrokji, Rami S.; Kulasekararaj, Austin; Al Ali, Najla H.; Kordasti, Shahram; Bart‐Smith, Emily; Craig, Benjamin M.; Padron, Eric; Zhang, Ling; Lancet, Jeffrey E.; Pinilla‐Ibarz, Javier; List, Alan F.; Mufti, Ghulam J.; et al.
Abstract : Immune dysregulation and altered T‐cell hemostasis play important roles in the pathogenesis of myelodysplastic syndromes (MDS). Recent studies suggest an increased risk of MDS among patients with autoimmune diseases. Here, we investigated the prevalence of autoimmune diseases among MDS patients, comparing characteristics and outcomes in those with and without autoimmune diseases. From our study group of 1408 MDS patients, 391 (28%) had autoimmune disease, with hypothyroidism being the most common type, accounting for 44% ( n  = 171) of patients (12% among all MDS patients analyzed). Other autoimmune diseases with ≥5% prevalence included idiopathic thrombocytopenic purpura in 12% ( n  = 46), rheumatoid arthritis in 10% ( n  = 41), and psoriasis in 7% ( n  = 28) of patients. Autoimmune diseases were more common in female MDS patients, those with RA or RCMD WHO subtype, and those who were less dependent on red blood cell transfusion. Median overall survival (OS) was 60 months (95% CI, 50–70) for patients with autoimmune diseases versus 45 months (95% CI, 40–49) for those without (log‐rank test, P  = 0.006). By multivariate analysis adjusting for revised IPSS and age >60 years, autoimmune diseases were a statistically significant independent factor for OS (HR 0.78; 95% CI, 0.66–0.92; P  = 0.004). The rate of acute myeloid leukemia (AML) transformation was 23% ( n  = 89) in MDS patients with autoimmune disease versus 30% ( n  = 301) in those without ( P  = 0.011). Patient groups did not differ in response to azacitidine or lenalidomide treatment. Autoimmune diseases are prevalent among MDS patients. MDS patients with autoimmune diseases have better OS and less AML transformation. Am. J. Hematol. 91:E280–E283, 2016. © 2016 Wiley Periodicals, Inc.